Unveiling Parental Knowledge, Attitudes, and Practices on Intestinal Parasitic Infections in Lahore, Pakistan: Unveiling Parental Knowledge, Attitudes, and Practices on Intestinal Parasitic Infections - Zia, Kanwal; Hameed, Sajid; Pervaiz, Khizzer; Ahmad, Zeeshan; Butt, Asif Maqsood; Hamid Khan, Muhammad Hatim (Pakistan Journal of Health Sciences, 2024)
Intestinal Parasitic Infections are intestinal infections, especially in toddlers, caused by parasites such as worms. Objectives: To explore Knowledge, Attitudes, and Practices of Intestinal Parasitic Infections in Pakistan, emphasizing their interlinkage with other socio-demographic factors. Methods: This cross-sectional study was conducted in Pak town, Lahore, on 348 parents. A questionnaire was developed to record demographic data, five Knowledge items, seven Attitudes, and 12 Practice questions. IBM SPSS version 27 was used for all the analyses. Descriptive, chi-square and binary logistic regression analyses were applied. Results: The majority of participants were housewives (50.9%). The levels of Knowledge, Attitude, and Practices were poor in 56%, 60.9%, and 51.7% of the parents, respectively. There was a greater likelihood of good attitude in parents with good knowledge (adjusted OR=5.3; 95% CI=0.3-96.4) compared with poor knowledge. Male were less likely (adjusted OR=0.3; 95% CI=0.1-0.7) to present good attitudes than female. Parents with education level of Intermediate (adjusted OR=2.6; 95% CI=1.2-5.7), Graduate (adjusted OR=3.5; 95% CI=1.6-7.6), and Masters (adjusted OR=60.8; 95% CI=3.8-974.3) showed better attitudes than those with secondary education. Good practices were associated with the presence of good attitudes rather than poor attitudes (adjusted OR=0.6; 95% CI=0.4-0.9). Conclusions: It was concluded that there was a poor prevalence of Knowledge, Attitudes, and Practices in Punjab. Good knowledge determines good attitudes that control good practices; hence, a focus on augmenting Practices of Intestinal Parasitic knowledge among parents should be the top priority of healthcare, especially among mothers.